Effects of Food Bioactive Compounds on Human Health and Disease Prevention in Botswana - Larona, Mercy (International Journal of Food Sciences, 2024)
Purpose: The aim of the study was to evaluate effects of food bioactive compounds on human health and disease prevention in Botswana. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The study found that bioactive compounds found in a variety of foods, including fruits, vegetables, grains, and herbs, have been extensively studied for their potential health benefits, including antioxidant, anti-inflammatory, and anti-cancer properties. In Botswana, where NCDs such as diabetes, hypertension, and cardiovascular diseases are major public health concerns, integrating bioactive-rich foods into the diet plays a crucial role in reducing the prevalence and impact of these conditions. Unique Contribution to Theory, Practice and Policy: Nutritional Epidemiology Theory, Pharmacological Theory of Food Bioactive Compounds & Health Behavior Theory may be used to anchor future studies on effects of food bioactive compounds on human health and disease prevention in Botswana. Promote public awareness and education campaigns to highlight the importance of incorporating bioactive compounds into daily diets for health maintenance and disease prevention. This can include disseminating accessible information about bioactive-rich foods and their health benefits. Advocate for the inclusion of dietary guidelines that emphasize the consumption of bioactive-rich foods in national nutrition policies. This can involve collaborating with policymakers to integrate evidence-based recommendations into dietary guidelines and public health initiatives.